A global view of atmospheric ice particle complexity. Issue 22 (26th November 2016) - Schmitt, Carl G.; Heymsfield, Andrew J.; Connolly, Paul; Järvinen, Emma; Schnaiter, Martin
Abstract: Atmospheric ice particles exist in a variety of shapes and sizes. Single hexagonal crystals like common hexagonal plates and columns are possible, but more frequently, atmospheric ice particles are much more complex. Ice particle shapes have a substantial impact on many atmospheric processes through fall speed, affecting cloud lifetime, to radiative properties, affecting energy balance to name a few. This publication builds on earlier work where a technique was demonstrated to separate single crystals and aggregates of crystals using particle imagery data from aircraft field campaigns. Here data from 10 field programs have been analyzed and ice particle complexity parameterized by cloud temperature for arctic, midlatitude (summer and frontal), and tropical cloud systems. Results show that the transition from simple to complex particles can be as small as 80 µm or as large as 400 µm depending on conditions. All regimes show trends of decreasing transition size with decreasing temperature. Plain Language Summary: Ice particles and snow in clouds can take on many shapes. These shapes can be very simple such as the typical hexagonal shape so often associated with ice particles. In most cases though, ice particles are much more complicated in appearance. The shape and size of ice particles in clouds are very important for climate modeling as sunlight can reflect or pass through ice particles. In this study, we use a technique to evaluate the shapes of ice particles from data collected during aircraft field projects. The technique determines a "complexity" value. We evaluated data from numerous field projects around the world and found that larger ice particles are more complex than small ice particles. We also found that the typical switch from simple to complex ice particles happens at smaller sizes at colder temperatures. We provide relationships to estimate the transition size for clouds around the world. Key Points: Ice particle complexity is parameterized by temperature and cloud type Ten data sets show common trends by cloud type